1985
DOI: 10.1177/028418518502600203
|View full text |Cite
|
Sign up to set email alerts
|

Correlation with Clinical Examination, Mammography, Cytology and Histology

Abstract: Histologically classified benign breast disorder was present in 163 breast of 158 symptomatic women. The results of diaphanography (DPG) were correlated with those obtained by clinical examination (CE), mammography (M) and cytology (C). A tumour was palpable in 108 cases (66.3%). A false positive diagnosis, i.e. possibly malignant, probably malignant or malignant was made in 15 cases (9.2%) with DPG, and in 33 cases (20.2%) with M. Use of both M and DPG reduced the number of false positives to 1.8 per cent. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…͑The literature is often vague in distinguishing transillumination/lightscanning from diaphan-ography. Typically, transillumination refers to white-light illumination, whereas diaphanography refers to red and NIR illumination.͒ Some studies, most notably those of Bartrum and Crow, 3 Wallberg et al, 4 and Budred et al, 5 have shown very favorable results comparing optical and radiological devices as screening tools. Other studies, most notably by Drexler, Davis, and Schofield, 6 Monsees, Destouet, and Gersell, 7 and Alveryd et al 8 have shown quite the opposite.…”
Section: History Of Early Breast Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…͑The literature is often vague in distinguishing transillumination/lightscanning from diaphan-ography. Typically, transillumination refers to white-light illumination, whereas diaphanography refers to red and NIR illumination.͒ Some studies, most notably those of Bartrum and Crow, 3 Wallberg et al, 4 and Budred et al, 5 have shown very favorable results comparing optical and radiological devices as screening tools. Other studies, most notably by Drexler, Davis, and Schofield, 6 Monsees, Destouet, and Gersell, 7 and Alveryd et al 8 have shown quite the opposite.…”
Section: History Of Early Breast Opticsmentioning
confidence: 99%
“…Knowledge of the absorption spectrum provides the information needed to solve a weighted least-squares problem to recover the concentrations of the four principal NIR absorbers in tissues: Hb-R, 4 . Since it is difficult to quantify lipids in terms of a concentration, the molar extinction coefficients were used as cm 2 Kg…”
Section: Calculation Tissue Physiology: Absorptionmentioning
confidence: 99%
“…Optical methods applied to breast imaging in the 1980s consisted of trans-illumination and diaphanography, which used continuous-wave visible and NIR light, respectively, to visualize lesions [3]. These qualitative approaches did not account for the strongly scattering nature of NIR light propagation in tissue that led to high false negative and false positive rates and contradictory findings [4][5][6][7][8][9]. Advances in the understanding of light transport through turbid media during the 1990s led to the development of technologies based on DOS and diffuse optical imaging (DOI).…”
Section: Basic Principles Of Near-infrared Diffuse Optical Spectroscopymentioning
confidence: 99%
“…One of the reasons for this could be that fibroadenomas might have increased concentrations of erythrocytes even if the average concentration in carcinoma is reported to be higher (15). Also, inflammatory breast diseases, hema tomas, necroses, and cysts with bloody contents m a y mark edly reduce the transmittance of light, thus mimicking a malignant lesion (16).…”
Section: Discussionmentioning
confidence: 99%